The relationship between sleep duration and physical activity level among Norwegian adolescents: a cross-sectional study - Grasaas, Erik; Hysing, Mari; Sandbakk, Øyvind (Frontiers in Public Health, 2024)
BackgroundFailure to adhere to sleep and physical activity recommendations among adolescents constitutes a public health problem. However, the associations between sleep duration and adolescents’ physical activity levels remain less explored. The aims of this paper were twofold: (1) to describe sleep and physical activity levels among Norwegian school-based adolescents, stratified by school level and sex and (2) to explore the association between sleep and physical activity levels.MethodsData were derived from the 2022 Norwegian Ungdata Survey, totaling 63,113 adolescents from lower (aged 13 to 16 years) and upper (aged 16 to 19 years) secondary schools. Study variables were measured using single-item questions from the Ungdata survey and collected through an electronic questionnaire administered during school hours. Logistic regressions were performed using crude analysis and adjusted for Socioeconomic status (SES) and grade level (age).ResultsIn lower secondary school, 57.0% of girls and 44.7% of boys reported sleeping less than the recommended 8 h, whereas in upper secondary school, the rate was 74.9% among girls and 74.3% among boys. Girls consistently reported more sleep problems, feeling more tired at school or during activities, and less physical activity than boys across school levels. Sleep duration was a significant predictor for all levels of weekly physical activity among girls across school levels, with the highest odds revealed in upper secondary school among those being active 5 times a week (B = 1.32; 95% CI [1.24 to 1.40]). Sleep duration was a predictor for being active 5 times a week for boys across school levels (B = 1.22; 95% CI [1.17 to 1.27]).ConclusionAbout half of younger adolescents and three-quarters of older adolescents do not adhere to the sleep recommendation. Lower levels of physical activity were consistently reported by girls than boys. Sleep duration consistently predicted a 20 to 30% higher likelihood of being active at least 5 days a week across sex and school levels. These findings underscore the critical role of sleep duration relations to higher physical activity levels among Norwegian adolescents. Government and policymakers should encourage healthy sleep and PA habits by explicitly incorporating guidelines into the curriculum.